Assessing standard costs in local public bus transport: Evidence from Italy. (November 2016) - Avenali, Alessandro; Boitani, Andrea; Catalano, Giuseppe; D'Alfonso, Tiziana; Matteucci, Giorgio
Abstract: We present a regression model for estimating unit standard costs for the Italian local public bus transport services. We account for quantitative and qualitative characteristics, which contribute to explain the variability of the cost structure. Economic and transport data have been collected from companies producing more than 500 million of bus-kilometers. We find that commercial speed is the most important cost driver, while economies of scale are low and only present in small size services. Results prove a positive correlation between investments in bus fleet and the cost incurred in service provision. Finally, we show how the regression model can be augmented with policy targets in order to fairly allocate among Italian Regions the public funds yearly earmarked to the local public transport sector. Highlights: We estimate, by a regression model, standard costs for local public bus transport. We focus on Italy and consider quantitative and qualitative characteristics. Commercial speed is the most important cost driver. Economies of scale are low and only present in the case of small sized services. Investments in bus fleet and the cost of the service are positively correlated.